Treatment of dural sinus thrombosis by urokinase infusion. - Smith, T P; Higashida, R T; Barnwell, S L; Halbach, V V; Dowd, C F; Fraser, K W; Teitelbaum, G P; Hieshima, G B (American Journal of Neuroradiology, 1994)
PURPOSE To gain a preliminary understanding of the role of thrombolytic therapy for the thrombosed dural sinus, we retrospectively reviewed our initial experience. METHODS Seven patients, ages 25 to 71, who presented with symptomatic dural sinus thrombosis and who failed a trial of medical therapy were treated with direct infusion of urokinase into the thrombosed sinus. Patients received urokinase doses ranging from 20,000 to 150,000 U/h with a mean infusion time of 163 hours (range 88 to 244 hours). RESULTS Patency of the affected dural sinus was achieved with antegrade flow in all patients. Six patients either improved neurologically over their prethrombolysis state or were healthy after thrombolysis; one of them required angioplasty. The other patient improved after surgical repair of a residual dural arteriovenous fistula. The only complications were an infected femoral access site which resolved after treatment with antibiotics and hematuria which cleared after discontinuation of anticoagulation. CONCLUSIONS Thrombolysis of the thrombosed dural sinus shows promise as a safe and efficacious treatment. The results of this study should provide the impetus for further research.